Examining University Students’ Self-Compassion and Compassionate Love Levels in Terms of Perceived Parental Attitudes - Eker, Halime; Kaya, Mehmet (My University, 2018)
The aim of this research is to investigate the relationship between parental attitudes perceived by the students, self-compassion and compassionate love levels, and differences occur in parental attitudes, self-compassion and compassionate love levels according to various variables. The research was conducted with 326 university students studying in different departments of Sakarya University Faculty of Education. Parental Attitude Scale (PAS), Self-Compassion Scale (SCS), the Compassionate Love Scale (CLS) and Information Collection Form were applied in the study. The research data were analyzed by correlation, T-test and One Way (ANOVA). The results of the research revealed that the self-compassion level of the students who perceived the parents' attitudes as democratic was high, whereas the self-compassion level of the students who perceived the parental attitudes as authoritarian and protective-demanding was low. It was also found out that the students who perceived their parents' attitudes as authoritarian and protective-demanding had high compassionate love levels. The present study demonstrated the authoritarian and protective-demanding parental attitudes perceived by university students differed according to sex, the democratic parental attitude differed in terms of the number of siblings, and the compassionate love differed in terms of gender. It was revealed that there was a negative relationship between self-compassion and compassionate love.
Keywords: parental attitudes; self- compassion; compassionate love